Indocyanine green dye enhanced laser photocoagulation for juxtafoveal choroidal neovascularisation - Hussain Nazimul; Hussain Anjli; Natarajan Sundaram (Indian Journal of Ophthalmology, 2005)
PURPOSE: To evaluate the initial results of pilot study of indocyanine green dye enhanced laser photocoagulation for juxtafoveal choroidal neovascularisation (CNV). MATERIALS AND METHODS: The study was conducted on eleven eyes of 11 patients of CNV during the period 2001 and 2002. Two to three minutes after the injection of 5 ml of 25 mgm of indocyanine green (ICG) dye, 810 nm diode laser was used to treat the choroidal neovascular lesions. RESULTS: The age of the patients ranged from 45 to 80 years. All patients completed 12 months of follow-up. Eight eyes (72.7%) had neovascular age related macular degeneration, 2 eyes (18.2%) had myopic CNV and one eye (9.09%) had CNV secondary to angioid streak. The presenting visual acuity was £ 6/60 in seven, 6/36 in one and ³ 6/12 in three patients. The final visual acuity at the end of at least 12 months follow-up was 6/12 or better in one eye (9%); 6/18-6/36 in 3 eyes (27.27%) and £ 6/60 in 7 eyes (63.64%). In four patients the vision improved whereas it worsened or remained same in 7 eyes. CONCLUSION: ICG dye enhanced diode laser photocoagulation appears to be a potential option for juxtafoveal CNV.